Analisis Faktor-faktor Pertumbuhan Laba pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Yeni Rahmadani; Isni Andriana; Kemas M. Husni Thamrin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to analyze the factors that influence profit growth in the banking sector listed on the Indonesia Stock Exchange. The population in this study were all banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019, which were 33 banking sector companies with a research sample of 8 companies. The sampling technique used was purposive sampling. The analysis technique used is multiple linear regression using SPSS. The results of this study indicate that the loan to deposit ratio (LDR) and return on assets (ROA) have a positive and significant effect on profit growth, operating expenses for operating income (BOPO) have a negative and significant effect on profit growth. Non-performing loan (NPL) has no significant effect on profit growth.